2014
DOI: 10.1063/1.4901947
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study on the effect of structural relaxation on the electronic and optical properties of P-doped Si nanocrystals

Abstract: A density functional theory-based study of the electronic structures and properties of cage like metal doped silicon clusters J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…After adding a few P atoms into Si NCs/SiO 2 multilayers (0.2%), the EX center defect signal became weak, which indicates the reduction of EX center concentration on the interfaces due to the passivation effect of P dopants located at the NCs surfaces. For the high P-doped sample (4%), a strong signal of conductor electrons is detected with a g value of 1.998, which attributes to partly P impurities located at the Si NCs lattice sites substitutionally providing free electrons [36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…After adding a few P atoms into Si NCs/SiO 2 multilayers (0.2%), the EX center defect signal became weak, which indicates the reduction of EX center concentration on the interfaces due to the passivation effect of P dopants located at the NCs surfaces. For the high P-doped sample (4%), a strong signal of conductor electrons is detected with a g value of 1.998, which attributes to partly P impurities located at the Si NCs lattice sites substitutionally providing free electrons [36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the similar preferential distribution of B and codoped B/P should occur as the NC size changes from 1.4 nm to a different one. It has been shown that the electronic structures of doped Si NCs critically depend on the doping-induced structural distortion [38,47]. When the NC size is 1.4 nm, Si NCs are less vulnerable to structural distortion [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Formation energy Figure 1 shows the model of a geometry-optimized 1.4-nm Si NC embedded in SiO 2 with (a) perfect Si/SiO 2 interface (Si@SiO 2 ) or (b) defective Si/SiO 2 interface at which a Si dangling bond exists (Si@ db SiO 2 ). The model of Si@SiO 2 is based on a 1.4-nm H-passivated Si NC (Si@H, Si 71 H 84 ), which has been detailed in our previous work [43][44][45][46][47]. An O atom is used to replace every H atom in SiH and SiH 3 at the surface of Si@H, which is then outwardly bonded to an added Si atom.…”
Section: B Dopingmentioning
confidence: 99%
“…In ref , it was shown that the formation energy of a single-Boron-doped nanostructure becomes saturated at the sizes larger than Si 147 H 100 . In ref , the formation energy of a Si nanostructure (Si 71 H 84 ) doped with 3 phosphorus dopants was 2.35 and 2.48 eV, respectively, for the cases without and with relaxation introduced by geometry optimization. The 0.13 eV binding energy difference (∼5%) between relaxed and unrelaxed structures was very small for such heavily doped systems.…”
Section: Methodsmentioning
confidence: 98%
“…Typically, 10 Å of vacuum separation was used in the cluster simulations reported elsewhere. 20 The dimensions of the unit cell are about 54 Å × 43 Å × 32 Å. The dimensions of the nanorod are about 34.3 Å × 23.4 Å × 12.5 Å, as indicated in Figure 1.…”
Section: ■ Methodsmentioning
confidence: 98%